2019
DOI: 10.1590/1980-5373-mr-2019-0057
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Nanocomposite Edible Films Based on Polysaccharides and Vitamin C from Agroindustrial Residue

Abstract: The agroindustrial residue from the production of acerola pulp is rich in residual vitamin C. Thus, aiming its extraction and stabilization, this work proposed the nanoparticle (NP) encapsulation via ionic gelation with subsequent preparation of nanocomposites (NC) film based on galactomannan matrix. NP were characterized and their stabilities were evaluated under different storage conditions (incidence of light, temperature and oxidizing atmosphere). The results by Dynamic Light Scattering (DLS) and Scanning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 40 publications
2
8
0
Order By: Relevance
“…For skin grape extract, there was a sharp downward trend in size for larger reactional volume. Finally, for acerola extract, the first and last reactional volumes were similar regarding NP size (Nascimento et al, 2019). According to the results, it is found a close similarity for NP size distribution between the first and the last reactional volumes studied.…”
Section: Nanoparticle Size and Zeta Potential In The Scale-upsupporting
confidence: 57%
See 1 more Smart Citation
“…For skin grape extract, there was a sharp downward trend in size for larger reactional volume. Finally, for acerola extract, the first and last reactional volumes were similar regarding NP size (Nascimento et al, 2019). According to the results, it is found a close similarity for NP size distribution between the first and the last reactional volumes studied.…”
Section: Nanoparticle Size and Zeta Potential In The Scale-upsupporting
confidence: 57%
“…Thus, it is important to evaluate the possibility of direct nanoencapsualtion of such substance from the aqueous extract. This can be carried out, for example, from acerola byproduct, once a previous study showed that in the processed residue still has a significant amount of residual vitamin C (Nascimento et al, 2019). Likewise, for winery byproducts, many phenolic compounds remain in the residue (Melo et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Such substances can be incorporated in FVBGFs by appropriate technological interventions such as vitamin D3 encapsulated edible nanoemulsions in milk 84 or vitamin C laden nanocomposite films formed by ionic gelation. 85 Living organisms/probiotics These days, people are ready to make severe changes in their diet to boost their health. This has led to an increase in purchase and intake of probiotic-rich foods.…”
Section: Nutraceuticalsmentioning
confidence: 99%
“…In another study, nanoparticle encapsulation of vitamin C by ionic gelation followed by preparation of nanocomposite film represented a decline in degradation of vitamin C thereby culminating in more than 30% storage of vitamin as compared with the control after 15 days of storage. Furthermore, on exposure to high temperature, 80% of the original concentration was retained (Nascimento et al, 2019). It was demonstrated that coating of fish oils by chitosan safeguarded the emulsified fish oils from the action of gastric enzymes, therefore ensuring their controlled release in the intestine (Chang et al, 2018).…”
Section: Nutraceuticalsmentioning
confidence: 99%